"I forgive but do not forget": A Systematic Review of Factors Influencing Forgiveness in Older Adults - Arafah, Fajriah Rahmah B; Ginanjar, Adriana Soekandar (Buletin Psikologi, 2025)
Forgiveness in the elderly is a complex process influenced by various internal and external factors. Studies on forgiveness in older adults highlight that time, life experiences, and individual characteristics play crucial roles in understanding and practicing forgiveness. This narrative literature review aimed to explain the factors influencing forgiveness in older individuals. The review included eight studies that met the specified inclusion criteria: discuss forgiveness, studying elderly individuals, and published within the last ten years 2014 to 2024. The literature review identified several factors affecting forgiveness in the elderly: (a) religiosity; (b) aging characteristics; (c) time; (d) the nature of transgressions; and (e) obligation to societal and cultural norms. Further exploration of the process of forgiveness among older adults is recommended for future research